2021
DOI: 10.5194/bg-2021-102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong temporal variation in treefall and branchfall rates in a tropical forest is explained by rainfall: results from five years of monthly drone data for a 50-ha plot

Abstract: Abstract. A mechanistic understanding of how tropical tree mortality responds to climate variation is urgently needed to predict how tropical forest carbon pools will respond to anthropogenic global change, which is altering the frequency and intensity of storms, droughts, and other climate extremes in tropical forests. We used five years of approximately monthly drone-acquired RGB imagery for 50 ha of mature tropical forest on Barro Colorado Island, Panama, to quantify spatial structure, temporal variation, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Beyond ALS, high-resolution imagery from other remote sensing platforms such as drones and satellites can also be used to track gaps through time, resulting in much richer time-series of canopy dynamics (Dalagnol et al, 2019;Cushman et al, 2021). For instance, Araujo et al (2021) collected monthly drone imagery over 5 years at Barro Colorado Island in Panama and found that treefall events mostly occurred during periods of extreme rainfall accompanied by high winds and lightningresulting in gap dynamics that are highly spatially and temporally clustered (Fisher et al, 2008;Negrón-Juárez et al, 2010). As our remote sensing toolbox continues to expand, so too will our ability to detect the fingerprint of different disturbance agents on the structure of forests (Milodowski et al, 2021;Nunes et al, 2021).…”
Section: Beyond Size Structure: Spatiotemporal Patterns Of Gap Formation and Dynamicsmentioning
confidence: 99%
“…Beyond ALS, high-resolution imagery from other remote sensing platforms such as drones and satellites can also be used to track gaps through time, resulting in much richer time-series of canopy dynamics (Dalagnol et al, 2019;Cushman et al, 2021). For instance, Araujo et al (2021) collected monthly drone imagery over 5 years at Barro Colorado Island in Panama and found that treefall events mostly occurred during periods of extreme rainfall accompanied by high winds and lightningresulting in gap dynamics that are highly spatially and temporally clustered (Fisher et al, 2008;Negrón-Juárez et al, 2010). As our remote sensing toolbox continues to expand, so too will our ability to detect the fingerprint of different disturbance agents on the structure of forests (Milodowski et al, 2021;Nunes et al, 2021).…”
Section: Beyond Size Structure: Spatiotemporal Patterns Of Gap Formation and Dynamicsmentioning
confidence: 99%
“…Disturbances are critical for explaining forest size distributions (Farrior et al, 2016) and have important implications for successional dynamics, as increased light levels in the understory favor fast‐growing light‐demanding species (Brokaw, 1987). Given that a significant proportion of canopy turnover is attributed to disturbance‐driven crown damage (Araujo et al, 2021; Chambers et al, 2001), representing this process is important for correctly estimating size distributions, and the impact of canopy gaps on recruitment and succession. Further, periodic, severe disturbances can cause high levels of defoliation and branch loss (Liu et al, 2018) with impacts that can last for months (Lodge et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…We compared the canopy area damaged each year, and the ratio of mortality to damage canopy turnover from simulations with observations of branch fall from repeated drone measurements over BCI (from Araujo et al (2021)). Tree size distributions were also compared with the full BCI census data, census interval 2010–2015 (Condit et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations